Vehicles construction control in district area / Mohd Ridzuwan Firdaus Mat Rashid - Mat Rashid, Mohd Ridzuwan Firdaus (Faculty of Architecture, Planning and Surveying, 2013)
The construction industry was the industry that had been develop a few years ago and it still in the progress because of our country status as a developing country. Besides that, parallel to the development of the construction industry, there are also the increases of the pollution in the construction due to the human error or the lack of the monitoring by the local authority. The monitoring of the machinery that was used in the construction also need to be considered because the machinery also can be the contributor to the pollution. The objective of this study was to identify the factor that contribute to the pollution, to identify the regulation and act, and to make the recommendation and conclusion on the issues that had happen around and in the construction site about the pollution. All of this matter will be create through several questionnaire and some observation that will be make at the construction site.